The study of participatory management practices (PMP) within the lean manufacturing - Camacho Carvajal, Luis Felipe (Working Papers, 2020)
Despite the increased adoption of automated and other technologies, participatory management practices (PMP) are becoming more critical in today’s workplaces. However, past social theories are inadequate in contributing to this discussion, as they fail to recognize that technology and automation can coexist with PMP processes within firms. This working paper aims to revise PMP approaches and worker experiences with PMP within the Lean manufacturing system of production. A new revision of PMP and workers’ experiences may shed light on new conceptual frameworks regarding dignity at work.